The impact of utilizing mobile phones to promote physical activity among post-secondary students: a scoping review - Ly, Hieu (mHealth, 2016)
A commitment to regular physical activity may reduce the risks of chronic diseases for young adults. Internationally, the majority of post-secondary students are insufficiently active for health benefits. Novel health strategies and interventions utilizing mobiles phones could increase post-secondary students’ physical activity levels. However, there is contradictory evidence to support the use of mobile phones to promote physical activity, and a scoping review could provide further insights into this topic. The purpose of this study was to conduct a scoping review to explore the existing literature and investigate what is currently known about the use of mobile phones to enhance physical activity levels among post-secondary students. A total of 84 articles were identified from the literature search, and six studies were selected for data analysis. Two major themes were supported by the evidence, which included: (I) the relationship between mobile phones and physical activity levels; and (II) students’ perceptions of mobile phones. Goal setting principles combined with text message interventions were reported to have significant influences on students’ physical activity levels. Students expressed mixed feelings about coaching elements of apps and posting personal results on social networking websites. No studies reported the use of objective physical activity measurements. In conclusion, mobile phone technologies such as text message reminders could be included in health interventions to enhance post-secondary students’ physical activity levels. There is limited evidence available on this topic and additional research is warranted to establish a clearer understanding of the relationship between mobile phones and post-secondary students’ physical activity.